Braking of Three Phase Induction Motors by Controlling Applied Voltage and Frequency Based on Particle Swarm Optimization Technique - Mahmoud Mohamed Elkholy; Mohammed Abd Elhameed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Braking of three phase induction motors is required in many industrial applications. This paper introduces braking of three phase induction motors using particle swarm optimization (PSO) technique. The objective is to determine the optimum values of the applied voltage and frequency during braking to stop the motor in a certain time with minimum braking energy losses to limit any excessive thermal heating. The proposed technique is important and more useful in applications of repeated braking cycles. The results are compared with that obtained using plugging braking method and it's found that the proposed technique gives lower braking energy and shorter braking time. The braking energy losses with the proposed method are about 20% of the plugging braking energy losses with the same braking time. The proposed method determines the variation of optimal values of applied voltage and frequency to have a certain braking time of three phase induction motor at a certain load torque with minimum braking energy losses. The characteristics of the motor are simulated using SIMULINK/MATLAB.